Influence of sowing date on growth and yield of summer mungbean varieties - Miah, Md. Abu Kawsar; Anwar, Md. Parvez; Begum, Mahfuza; Juraimi, Abdul Shukor; Islam, Md. Anwarul (Friends Science Publishers, 2009)
Four mungbean [Vigna radiata (L.) Wilczek] varieties viz. BINA moog2, BINA moog5, BINA moog6 and BINA moog7 were sown at 10 day intervals starting from 20 February to 11 April to identify the suitable variety (s) and optimum sowing date for getting maximum yield of summer mungbean. Among the varieties BINA moog7 was ranked first in terms of seed yield (938.40 kg ha-1) followed in order of BINA moog6 (711.72 kg ha-1), BINA moog5 (684.00 kg ha-1) and BINA moog2 (547.80 kg ha-1). BINA moog6 matured earlier than the other three varieties. The highest seed yield (969.62 kg ha-1) was obtained from 2 March sowing followed by 20 February (917.54 kg ha-1) and 12 March sowing (869.52 kg ha-1). Sowing after 2 March gradually decreased the seed yield producing the lowest value (388.87 kg ha-1) at 11 April sowing. In general, delayed sowing enhanced the maturity. BINA moog7 yielded the highest (1201.32 kg ha-1) when sown on 2 March, which was statistically similar to 20 February and 12 March sowing. Therefore, summer mungbean variety BINA moog7 may be sown during the period from 20 February to 12 March for higher seed yield and for late sowing, BINA moog6 may be considered as it matures earlier than others.